Pulmonary manifestations in Niemann-Pick type C disease with mutations in NPC2 gene: case report and review of literature. Issue 1 (December 2017) - Sheth, Jayesh; Joseph, Jijo; Shah, Krati; Muranjan, Mamta; Mistri, Mehul; Sheth, Frenny
Abstract Background Niemann-Pick disease type C (NPC) is an inherited metabolic disorder; due to defect in cellular cholesterol trafficking. It is clinically a heterogeneous disease with variable age of onset with multiple organ systems being involved.NPC1 gene is involved in 95% cases where as remaining ~5% cases are linked withNPC2 gene. Case presentation Case-1, a 14-months-old female presented with recurrent respiratory distress, failure to thrive and hepatosplenomegaly. Lung biopsy was suggestive of alveolar proteinosis and liver biopsy confirmed foamy macrophages. Molecular analysis revealed homozygous mutation c.141C > A in exon 2 ofNPC2 gene. Case-2, a 3-year-old male presented with dyspnoea and hepatomegaly noticed at 1 year of age. HRCT-scan of thoracic region showed consolidation with mediastinal lymphadenopathy. Broncho-alveolar lavage revealed moderate amount of foamy macrophages and bone marrow examination detected foam cells. Homozygous T > C transition in intron 1 of theNPC2 gene was identified. Conclusion Our study demonstrates that NPC2 can present in early years of life with pulmonary complications like alveolar proteinosis and hepatosplenomegaly or hepatomegaly due to mutation inNPC2 gene. An early suspicion will help clinicians to clinch its diagnosis, management and genetic counselling.